The Missing Body–Yoga and Higher Education - Judith Beth Cohen (Journal of the Assembly for Expanded Perspectives on Learning, 2006)
Using her own yoga practice as a basis, this author argues for more bodily involvement in learning and offers several exercises she has used to accomplish this.